Determinação dos coeficientes de cultura da alface (Lactuca sativae L.) - Bastos, Edson Alves; Lunardi, Dalva Martinelli Cury; Andrade Júnior, Aderson S. de; Aguiar Netto, Antenor de O. (IRRIGA, 1996)
Determinação dos coeficientes de cultura da alface (Lactuca sativae L.)